Influence of circular RNA topology on microRNA stability - Fuchs Wightman, Federico (2022)
A subset of circular RNAs (circRNAs) and linear RNAs have been proposed to “sponge” or block microRNA activity. Additionally, certain RNAs induce microRNA destruction through the process of Target RNA-Directed MicroRNA Degradation (TDMD), but whether both linear and circular transcripts are equivalent in driving TDMD is unknown. Here we study whether circular/linear topology of endogenous and artificial RNA targets affects TDMD. Consistent with previous knowledge that Cdr1as (ciRS-7) circular RNA protects miR-7 from Cyrano-mediated TDMD, we demonstrate that depletion of Cdr1as reduces miR-7 abundance. In contrast, overexpression of an artificial linear version of Cdr1as drives miR-7 degradation. Using plasmids that express a circRNA with minimal co-expressed cognate linear RNA, we show differential effects on TDMD that cannot be attributed to the nucleotide sequence, as the TDMD properties of a sequence often differ between its circular and linear forms. By analysing RNA sequencing data of a neuron differentiation system, we further detect potential effects of circRNAs on microRNA stability. Our results support the view that RNA circularity influences TDMD, either enhancing or inhibiting it on specific microRNAs.